Analisis Break Even Point Usahatani Pengolahan Kopra di Kecamatan Tidore Utara, Kota Tidore Kepulauan - Fatmawati Kaddas; Karmila Ibrahim; Iriani Basri (Universitas Khairun, 2023)
This study aims to determine how much income and feasibility of copra processing business in North Tidore District, Tidore Islands City. The research was conducted on copra processing farmers with a sample determination in North Tidore District using simple random sampling with a total of 64 respondents. The results showed that copra processing costs obtained an average value of Rp.2,065,274/year, consisting of fixed costs of Rp.498,967/year and variable costs of Rp.1,566,307/year. The average income is IDR 9,003,500/year and profits are IDR 6,938,226/year. Analysis of the feasibility of the copra processing business in North Tidore District, Tidore Islands City, for the average respondent, the R/C ratio value was 4.3, which means efficiency because for every Rp. 1 spent, a benefit of Rp. 4,3. The results of the BEP Break Even Point price obtained a value of Rp.1,261, a production BEP obtained a value of 109.8 kg and BEP revenue obtained a value of Rp.604,051.74 This means that the copra business is feasible to cultivate.Keywords: Processing, Copra, Break Even Point